Bismuth Reduces Cisplatin-Induced Nephrotoxicity Via Enhancing Glutathione Conjugation and Vesicular Transport - Jiang, Hui; Hong, Yifan; Fan, Guorong (Frontiers in Pharmacology, 2022)
Bismuth drugs have long been used against gastrointestinal diseases, especially gastric infection of Helicobacter pylori. Cisplatin is a widely used anti-cancer drug that tends to accumulate at renal proximal tubules and causes severe nephrotoxicity. It was found that bismuth pretreatment reduces cisplatin-induced nephrotoxicity, but mechanism of action remains unclear. To understand bismuth’s effect on renal tubules, we profiled the proteomic changes in human proximal tubular cells (HK-2) upon bismuth treatment. We found that bismuth induced massive glutathione biosynthesis, glutathione S-transferase activity and vesicular transportation, which compartmentalizes bismuth to vesicles and forms bismuth-sulfur nanoparticles. The timing of glutathione induction concurs that of bismuth-induced cisplatin toxicity mitigation in HK-2, and bismuth enhanced cisplatin sequestration to vesicles and incorporation into bismuth-sulfur nanoparticles. Finally, we found that bismuth mitigates the toxicity of general soft metal compounds, but not hard metal compounds or oxidants. It suggests that, instead of through oxidative stress reduction, bismuth reduces cisplatin-induced toxicity by direct sequestration.